2001
DOI: 10.1016/s0006-3495(01)76069-9
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid-to-Chlorophyll Energy Transfer in Recombinant Major Light-Harvesting Complex (LHCII) of Higher Plants. I. Femtosecond Transient Absorption Measurements

Abstract: The energy transfer kinetics from carotenoids to chlorophylls and among chlorophylls has been measured by femtosecond transient absorption kinetics in a monomeric unit of the major light-harvesting complex (LHCII) from higher plants. The samples were reconstituted complexes with different carotenoid contents. The kinetics was measured both in the carotenoid absorption region and in the chlorophyll Q(y) region using two different excitation wavelengths suitable for selective excitation of the carotenoids. Analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
216
2
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 210 publications
(241 citation statements)
references
References 56 publications
(89 reference statements)
21
216
2
2
Order By: Relevance
“…Slow (ps) Chl b fi Chl a energy transfer has also been reported for native complexes in the literature (Bittner et al 1994(Bittner et al , 1995Visser et al 1996;Connelly et al 1997;). The obtained transfer times for Chl b fi Chl a transfer in Lhcb1 (see Table 2) are somewhat different from those obtained by Croce et al (2001). They reported transfer times of 0.13, 0.33, 1 and 7 ps.…”
Section: Energy Transfercontrasting
confidence: 67%
See 1 more Smart Citation
“…Slow (ps) Chl b fi Chl a energy transfer has also been reported for native complexes in the literature (Bittner et al 1994(Bittner et al , 1995Visser et al 1996;Connelly et al 1997;). The obtained transfer times for Chl b fi Chl a transfer in Lhcb1 (see Table 2) are somewhat different from those obtained by Croce et al (2001). They reported transfer times of 0.13, 0.33, 1 and 7 ps.…”
Section: Energy Transfercontrasting
confidence: 67%
“…at around 660 nm Visser et al 1996Visser et al , 1997Gradinaru et al 1998), but at the same time an ultrafast process has been reported, although it was not unambiguously ascribed to Chl fi Chl energy transfer due to the long pulses used in the experiments (200-250 fs) (Visser et al 1996;Gradinaru et al 1998). Recently, Croce et al (2001) performed a detailed transient absorption (TA) study on one of the reconstituted isoforms of LHC II, namely Lhcb1. They reported for both carotenoid to chlorophyll and chlorophyll to chlorophyll similar transfer times and efficiencies to those of native LHC II complexes.…”
Section: Introductionmentioning
confidence: 99%
“…50 It has also been found in the case of monomeric systems and actually shows up more pronounced in studies with reconstituted systems. 47,48,51 However, as stated above, in the case of LHCI proteins, a similar component was found in both native and reconstituted systems. It is tempting to consider this loss channel to have the same origin as that found in the native PSI-LHCI particles.…”
Section: Discussionsupporting
confidence: 57%
“…The carotenoid to Pc energy transfer in dyad 1 is reminiscent of several natural light-harvesting antennas where high carotenoid to chlorophyll energy transfer efficiency is obtained by employing a multiphasic Car to Chl energy transfer. 2,11,21,[31][32][33] The final EADS (magenta line) appears after 2 ns and represents the component that does not decay on the time scale of the experiment. It features the typical carotenoid triplet ESA in the 475-550 nm region as well as a bleach/band-shift-like signal in the Pc Q region.…”
Section: Dyadmentioning
confidence: 99%